A New Model of Genetic Zone Routing Protocol (GZRP): The Process of Load Balancing and Offloading on The UMTS-IEEE 802.11g Hybrid Networks - Setiyo Budiyanto; Arissetyanto Nugroho (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The stages of the process of Genetic Algorithm (GA), are: Encoding Genotype and Chromosome; Set Initialization Population; Evaluation Fitness Function; and Selection Process as well as in the later stages Cross Over Process and Mutation. Outputs from the tests performed in this study can be obtained by comparing the Genes of the "Child" (condition data traffic on the UMTS Hybrid - 802.11g network after the GA) against Gen "Holding" (traffic data before the GA process). The research was conducted by calculating the environmental factors, namely: The scheme Two - Ray Model Propagation and Overlapping Channel Interference Factor, the Doppler Effect be ignored because the User Equipment (UE) is considered not to shift significant arenas on the IEEE 802.11g networks. The results of the research is as follows: In the process of cross over, there is a significant change in the bandwidth, data traffic capacity and Power parameter changes by 9 MHz,  36 MB, and 40 dBm. In the process of mutation, there is a significant change in the  bandwidth, data traffic capacity, and Power  parameter by 17 MHz, 32 MB, and 20 dBm.